Working process of TU 3a CNC frais machine using software system - J, Junaidi (International Journal of Engineering and Technology, 2020)
This workpiece process is: to find out how to transfer images from Auto CAD software to the Q plus CELL Milling Cnc software, and to find out how to transfer programs from the CNC Milling QELL KELLER software to the TU 3A CNC milling machine. The making of this workpiece uses three main media, namely Auto CAD 2000 software, CNC Milling KELLER Q plus software, and TU 3A CNC milling machine. The process of making the workpiece starts from making the workpiece design in Auto CAD software which is then stored on the CDR via DFX data. The design of the workpiece contained in the CDR is then transferred to CNC Millling KELLER Q plus software via Geometry. in Geometry, the design of the workpiece is dimensioned. Completed from the Geometry the workpiece design is included in the Work plan to be processed so that it can be simulated to move to a CNC program to convert the graphical language into a numeric language so that it can be read by a CNC machine. The programming results from the CNC KELLER Q plus software are then recorded to be executed on the CNC TU 3A milling machine to obtain the workpiece in accordance with the design in AutoCAD. Programming results from CNC Milling KELLER Q plus software cannot be directly used on the TU 3A milling machine (EMCO), because the programming language used is different. Programming language in CNC Milling KELLER Q plus software uses the DIN 66025 standard, while the CNC TU 3A (EMCO) milling machine uses ISO standards, so it needs to be converted first.